Toxoplasma gondii infection possibly reverses host immunosuppression to restrain tumor growth - Chen, Jiating; Liao, Wenzhong; Peng, HongJuan (Frontiers in Cellular and Infection Microbiology, 2022)
Tumor cells can successfully escape the host immune attack by induction of immunosuppressive cells and expression of immunosuppressive molecules, leading to ineffective treatment of tumors and a poor prognosis for patients. Although immunotherapies have been designed to improve patient survival, more effective drugs and therapies are still needed to be developed. As an intracellular parasite, Toxoplasma gondii can trigger intense Th1 immune response in host cells, including up-regulating interleukin-12 (IL-12) and interferon-γ (IFN-γ) expression. Non-replicating uracil auxotrophic strains of T. gondii were used to safely reverse the immunosuppression manipulated by the tumor microenvironment. In addition to the whole lysate antigens, T. gondii secreted effectors, including Toxoplasma profilin, rhoptry proteins (ROPs), and dense granule antigens (GRAs) are involved in arousing the host’s antigen presentation system to suppress tumors. After the immunosuppression is relieved, tumor-associated myeloid cells, including macrophages and dendritic cells (DCs) are converted into immune-stimulatory phenotypes, showing a powerful Th1 immune response mediated by CD8+ T cell, then achieving target-killing of tumor cells and ultimately reducing the size and weight of tumor tissues. This review summarized the latest articles on the use of T. gondii in tumor treatments, including the activation of cellular immunity and the related signal pathways involved, which will help us understand why Toxoplasma gondii infection can restrain tumor growth.